Effects of Cyclocarya paliurus Aqueous and Ethanol Extracts on Glucolipid Metabolism and the Underlying Mechanisms: A Meta-Analysis and Systematic Review - Liu, Wei; Wu, You; Hu, Yuli; Qin, Shuai; Guo, Xiaoyuan; Wang, Minghui; Wu, Lili; Liu, Tonghua (Frontiers in Nutrition, 2020)
Background and aims: Cyclocarya Paliurus (CP) has been used as a herbal tea to treat diabetes mellitus and obesity for hundreds of years. Previous research suggests that CP specifically restores glycolipid metabolic homeostasis, and the two most studied preparations are aqueous and ethanol extracts. In order to verify the effect of CP on glycolipid metabolism in animal models with metabolic syndrome, a meta-analysis was performed, and the active components and underlying mechanisms were systematically reviewed. Methods: Four databases: PubMed, Web of Science, Embase, and Cochrane Library were searched to acquire potential literature. Data of blood glucose (BG) level, area under curve (AUC) of oral glucose tolerance test (OGTT), total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels were extracted as indicators of assessment of CP’s effects. Follow-up analyses including subgroup analysis, meta-regressions, and publication bias were also conducted. Results: A total of 96 papers were identified from databases and 11 papers including 31 data reports were involved in the meta-analysis. CP had a positive effect in down-regulating BG, AUC of OGTT, TC, TG, and LDL, and up-regulating HDL (P < 0.001, 95% confidence interval of standard mean difference did not incorporate the null value 0). The effect of the ethanol extract was greater than that of the aqueous extract. Conclusion: CP showed definite activity of regulating glycolipid metabolism in animal models, and it exerted its function through multiple mechanisms including but not limited to: 1) improving insulin resistance; 2) protecting pancreatic  cells; 3) decreasing inflammatory infiltration; and 4) anti-oxidative stress.